2014
DOI: 10.1002/hep.27219
|View full text |Cite
|
Sign up to set email alerts
|

Current epidemiology of hepatitis E virus infection in the United States: Low seroprevalence in the National Health and Nutrition Evaluation Survey

Abstract: dataset found a relatively high seroprevalence (21%) of hepatitis E virus (HEV) infection in the U.S. general population. Using data obtained within the NHANES 2009-2010 survey, where a high performance assay for HEV was used, we estimated the weighted seroprevalence of HEV infection among U.S. individuals 6 years and older. We also evaluated factors associated with HEV seropositivity. A total of 8,814 individuals were included in the analysis. The median age of study participants was 37 years (interquartile r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
91
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 49 publications
23
91
3
Order By: Relevance
“…Last, the proportion of patients with detectable anti‐HEV IgG declined over time during the study period from 1998 to 2011 (http://onlinelibrary.wiley.com/doi/10.1002/hep.28649/suppinfo). Other studies have also noted a decline in the prevalence of anti‐HEV IgG‐positive blood donors and individuals in the general population using the same assay . The reason for the declining seroprevalance in Western patients over time is unknown, but a consistent finding.…”
Section: Discussionmentioning
confidence: 78%
“…Last, the proportion of patients with detectable anti‐HEV IgG declined over time during the study period from 1998 to 2011 (http://onlinelibrary.wiley.com/doi/10.1002/hep.28649/suppinfo). Other studies have also noted a decline in the prevalence of anti‐HEV IgG‐positive blood donors and individuals in the general population using the same assay . The reason for the declining seroprevalance in Western patients over time is unknown, but a consistent finding.…”
Section: Discussionmentioning
confidence: 78%
“…The lower prevalence of anti-HEV in the animal handlers and blood donor population also may be due to the implementation of stringent universal precautions in the workplace and a declining prevalence of anti-HEV in the general population. Indeed, a recent analysis of the general U.S. population sampled in the NHANES study conducted between 2009 and 2010 reported an estimated anti-HEV prevalence of 6% (35). Although different assays with different performance characteristics were used for anti-HEV testing between studies (36), a recent comparison of the prevalence of anti-HEV in both NHANES panels with the same anti-HEV assay found a prevalence of 16.8% in the 1988-1994 panel and only 6.4% in the 2009-2010 panel, suggesting that the prevalence of anti-HEV in the United States has diminished (37).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence is 18.6% among those exposed to porcine livestock (4) and 10.4% in HIV-infected individuals (12). In the United States the reported prevalence is 6% (13), while in England the prevalence is only 0.04% among donors (7). The true number of infections is difficult to establish, since subclinical infections are common and probably outnumber clinical infections.…”
Section: Introductionmentioning
confidence: 99%